The Correlation of Serum Trace Elements and Heavy Metals with Carotid Artery Atherosclerosis in Maintenance Hemodialysis Patients - AŞICIOĞLU, EBRU (HUMANA PRESS INC, 2011)
Changes in essential trace elements and heavy metals may affect the atherosclerotic state of patients on maintenance hemodialysis (HD). The aim of the study was to evaluate the relation between the serum levels of some trace elements and heavy metals (iron, zinc, manganese, copper, magnesium, cobalt, cadmium, lead, and copper/zinc ratio) and carotid artery intima-media thickness (CIMT) in HD patients. Fifty chronic HD patients without known atherosclerotic disease and 48 age- and sex-matched healthy individuals were included in the study. The serum levels of trace elements (iron, zinc, manganese, copper, and magnesium) and heavy metals (cobalt, cadmium, and lead) were measured by Atomic Adsorption Spectrophotometer (UNICAM-929). CIMT was assessed by carotid artery ultrasonography. The serum levels of iron, zinc, and manganese were lower; levels of copper, magnesium, cobalt, cadmium, lead, and copper/zinc ratio were higher in HD patients compared to controls. CIMT in HD patients were higher than the control group (0.64 +/- 0.11 vs 0.42 +/- 0.05, p < 0.001). There was a significant negative correlation between CIMT and serum levels of zinc (r = -0.70, p < 0.01), iron (r = -0.71, p < 0.01), and manganese (r = -0.47, p < 0.01), while there was a significant positive correlation between CIMT and serum levels of copper (r = 0.63, p < 0.01), magnesium (r = 0.77, p < 0.01), cobalt (r = 0.63, p < 0.01), cadmium (r = 0.48, p < 0.01), lead (r = 0.38, p < 0.01), and copper/zinc ratio (r = 0.68, p < 0.01). A linear regression analysis showed that serum levels of magnesium, cadmium, lead, and copper/zinc ratio were still significantly and positively correlated with CIMT. We propose that copper/zinc ratio, magnesium and toxic metals cadmium and lead are independent determinants of CIMT in maintenance HD patients without known atherosclerotic disease.
Keywords: Atherosclerosis; Carotid artery; Cu/Zn ratio; Hemodialysis; Trace elements; INTIMA-MEDIA THICKNESS; HIGH BLOOD-PRESSURE; CARDIOVASCULAR-DISEASE; RISK-FACTOR; ASSOCIATION; KIDNEY; LEAD